Hepatotoxicity of fusariotoxins, alone and in combination, towards the HepaRG human hepatocyte cell line. (November 2017) - Smith, Marie-Caroline; Hymery, Nolwenn; Troadec, Samuel; Pawtowski, Audrey; Coton, Emmanuel; Madec, Stéphanie
Abstract: While the reality of mycotoxin co-occurrence in food commodities is now established, their effects in mixtures are not well studied. The present study investigated the individual and combined effects of deoxynivalenol (DON), nivalenol (NIV), T-2 toxin (T2), fumonisin B1 (FB1), zearalenone (ZEA) and moniliformin (MON) fusariotoxins on cell viability and cell death mechanisms in proliferating HepaRG cells, a human derived liver cell line. In addition, DON-ZEA being one of the most widespread mycotoxin mixtures in grains worldwide, its effect on the expression levels of genes encoding for sets of hepatocyte-specific functions was studied. After 48 h, T2 appeared to be the most cytotoxic tested fusariotoxins, followed by NIV, DON and ZEA. Furthermore, at low cytotoxic doses, all tested fusariotoxin mixtures (DON-MON, DON-FB1, DON-ZEA and NIV-T2) acted synergistically on cell death. Interestingly, during the first 18 h of exposure, only FB1 and ZEA alone and in combination with DON seemed to induce cell apoptosis and necrosis. At the gene level, after only 1 h, DON-ZEA combination induced expression of drug-metabolizing enzymes contrary to individual exposures. Thus, the observed synergy of fusariotoxin mixtures suggested that their simultaneous presence in food commodities can induce a toxic risk that should be better taken into consideration. Graphical abstract: Highlights: DON, NIV, T2 and ZEA reduced HepaRG cell viability in a dose-dependent manner, T2 being the most cytotoxic. All tested binary mixtures showed synergism on cell viability reduction after 48 h exposure. Only FB1 and ZEA alone and in combination with DON seemed to induce early cell apoptosis and necrosis after 18 h exposure. After only 1 h, DON-ZEA combination induced expression of drug-metabolizing enzymes contrary to single exposures.